PERAN KEPEMIMPINAN KEPALA SEKOLAH PADA IMPLEMENTASI STANDAR PROSES PEMBELAJARAN PENDIDIKAN DASAR - Ayu Setia Andarwati; Ngarifin Shiddiq; Sri Haryanto (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2022)
Primary education aims to lay the foundation of intelligence, knowledge, personality, noble character, and skills for independent living. Resources as the output of the educational process are required to produce intellectually and spiritually intelligent human help. Islamic-based Basic Education is one of the Educational Institutions with a vision of building spiritual intelligence and intellectual intelligence. Islamic-based school leadership has a very central role. This is stated in Surah Al-Anbiya’ chapter 73: